2013
DOI: 10.1007/s00216-013-7481-1
|View full text |Cite
|
Sign up to set email alerts
|

Online dynamic pH junction–sweeping for the determination of benzoic and sorbic acids in food products by capillary electrophoresis

Abstract: A simple, low-cost, and efficient online focusing method that combines a dynamic pH junction and sweeping by capillary electrophoresis with polymer solutions was developed and optimized for the simultaneous determination of benzoic acid (BA) and sorbic acid (SA). A sample solution consisting of 2.5 mM phosphate at pH 3.0 and a buffer solution containing 15 mM tetraborate (pH 9.2), 40 mM sodium dodecyl sulfate, and 0.100 % (w/v) poly(ethylene oxide) were utilized to realize dynamic pH junction-sweeping for BA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these additives can be obtained from nature or manufactured by the chemical industry. The main food additives analyzed by CE in the period covered by this review (2013–2015) were sweeteners , preservatives , and colorants .…”
Section: Food Additivesmentioning
confidence: 99%
“…Given the low concentration of preservatives in food samples different approaches have been employed to increase sensitivity. For instance, an online dynamic pH junction‐sweeping method was coupled to CE for the analysis of benzoic acid and sorbic acid . Dynamic pH junction together with sweeping demonstrated to significantly enhance sensitivity during CE analysis.…”
Section: Food Additivesmentioning
confidence: 99%
“…Apparatus: All experiments were performed using a laboratory-made unit similar to a previously described system, 31 …”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29][30][31] In order to reduce PEO adsorption on the capillary wall and thereby generate a high and repeatable EOF, the capillary is filled with 15 mM phosphate solution (pH 9.5) containing 20 mM SDS (Fig. 1A).…”
Section: On-line Concentration and Separation Of The Paraben Preservamentioning
confidence: 99%
“…Nevertheless, we observed the mixtures of benzoic and sorbic acid are used in some food products in Turkey. While several of the CE reports demonstrated the possibilities for simultaneous determination of benzoic and sorbic acids (Boyce, 1999;Frazier et al, 2000;Kuo & Hsieh, 1997;Lin et al, 2000;Pant & Trenerry, 1995;Waldron & Li, 1996;Han et al, 2008;Hsu et al, 2014;Sun et al, 2014;Li et al, 2015;Aung & Pyell 2016), only a few of them reported benzoic and sorbic acids together in real samples.…”
Section: Introductionmentioning
confidence: 99%